Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Pada Kantor Perum Perhutani Kph Ngawi) - Kurniasari, Evi Ika, Basworo Dibyo, S.E, M.Si (2015)
The purpose of this study was to determine the effect of motivation and work environment on the performance of employees in the office Perum Perhutani KPH Ngawi. This type of research is a quantitative research, with a population of all employees of the Office of Perum Perhutani KPH Ngawi totaling 73 employees as the population, with a sample of 43 people. Sampling using simple random sampling technique that members of the population sample was randomly without regard to strata that exist in the population. Research data collection techniques through a questionnaire with Likert scale. Based on Regression Analysis in mind that the value of the constant is positive in the amount of 6,146. This suggests that if in the absence of an independent variable motivation and work environment, the performance of employees will remain high. Based on the analysis found that the variable t test, motivation (3,257> 2,021) and work environment (4.578> 2.021) have an influence on the performance of employees in the Office of Perum Perhutani KPH Ngawi. Test results F 17.940> 3,23 so that in this study independent variables jointly affect the dependent variable. The coefficient of determination (R2) obtained R Square (R2) of 0.473, mean of 47.3% of the variation changes the performance variables can be explained by the variable of work motivation (X1) and work environment (X2). While sisannya amounted to 52.7% explained by other variables outside the model. Keywords: Work Motivation, Work Environment and Performance